2018
DOI: 10.1002/ece3.4384
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall seasonality and drought performance shape the distribution of tropical tree species in Ghana

Abstract: Tree species distribution in lowland tropical forests is strongly associated with rainfall amount and distribution. Not only plant water availability, but also irradiance, soil fertility, and pest pressure covary along rainfall gradients. To assess the role of water availability in shaping species distribution, we carried out a reciprocal transplanting experiment in gaps in a dry and a wet forest site in Ghana, using 2,670 seedlings of 23 tree species belonging to three contrasting rainfall distributions group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…This may explain why a previous global analyses did not find significant climatic effects on the hydraulic trade‐off based on mean annual precipitation and temperature (Gleason et al ., 2016b). Furthermore, the seasonality of precipitation, VPD, and SR trends reported here are also consistent with the water–energy hypothesis, which not only influences regional plant ecological adaptation strategies (Amissah et al ., 2018) but may also affect global plant diversity (Kreft & Jetz, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why a previous global analyses did not find significant climatic effects on the hydraulic trade‐off based on mean annual precipitation and temperature (Gleason et al ., 2016b). Furthermore, the seasonality of precipitation, VPD, and SR trends reported here are also consistent with the water–energy hypothesis, which not only influences regional plant ecological adaptation strategies (Amissah et al ., 2018) but may also affect global plant diversity (Kreft & Jetz, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since cellular protection is a priority during stress, it has been shown that some responses to dehydration and excess water have common molecular effectors acting as nodes in the crosstalk between responses to drought and submergence [ 9 , 10 , 11 ]. This may have allowed wild plants to evolve tolerance mechanisms to cope with alternate drought and flooding events, which commonly occur consecutively in some regions of the world [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…All bioclimatic variables are derived from the monthly or daily temperature and rainfall values in order to produce ecologically important variables used for niche modelling with high consistency (García-Callejas & Araújo 2016; Morales-Barbero & Vega-Álvarez 2019). The applied bioclimatic variables signify annual means (Booth 2016; Kendal et al 2018), seasonality (Hereford et al 2017; Tonkin et al 2017) and severe environmental factors (e.g., duration and severity of water excess and deficits) that influence species distribution and performance (e.g., Amissah et al, 2018).…”
Section: Methodsmentioning
confidence: 99%